2021
DOI: 10.1016/j.molmed.2021.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic maintenance of the lymphatic vasculature

Abstract: The lymphatic vasculature is an active multifaceted regulator of tissue homeostasis, growth, and regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 173 publications
(236 reference statements)
0
34
0
Order By: Relevance
“…Extending these findings to LVs, it is certain that these vessels similarly experience pro-survival signaling, the disruption of which can lead to LV regression ( Figure 3 ). Although the LV network experiences less shear stress than the BV network, Stritt et al (2021) showed that LVs have greater sensitivity to shear stress and further elucidated the mechanisms by which shear stress may lead to LEC proliferation in vitro . In addition to LEC proliferation and potential survival, shear stress has also been implicated in the survival of lymphatic valves ( Iyer et al, 2020 ).…”
Section: Learning From Blood Vessel Regressionmentioning
confidence: 97%
See 2 more Smart Citations
“…Extending these findings to LVs, it is certain that these vessels similarly experience pro-survival signaling, the disruption of which can lead to LV regression ( Figure 3 ). Although the LV network experiences less shear stress than the BV network, Stritt et al (2021) showed that LVs have greater sensitivity to shear stress and further elucidated the mechanisms by which shear stress may lead to LEC proliferation in vitro . In addition to LEC proliferation and potential survival, shear stress has also been implicated in the survival of lymphatic valves ( Iyer et al, 2020 ).…”
Section: Learning From Blood Vessel Regressionmentioning
confidence: 97%
“… Regulation of LV quiescence and growth in adults, reproduced from Stritt et al (2021) . Mechanisms that regulate the maintenance of LEC quiescence (upper left box) and the reactivation of LV growth and regeneration in adult tissues are depicted.…”
Section: Learning From Blood Vessel Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of lymph in the interstitial tissue leads to remodeling of the skin and subcutaneous tissue and the accumulation of fibroadipose tissue [ 7 ]. The chronic form of lymphedema is characterized by swelling, fibrosis, accumulation of adipose tissue and infiltration of immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…The signals, including cells, antigens, and cytokines, that lymphatic vessels do or do not transmit thus play critical roles in shaping immunity and autoimmunity. Lymphatic vessels begin as blind-ended capillaries in tissue, which reabsorb interstitial fluid and molecules (see [1,2] for recent reviews on lymphatic ontogeny, function and signalling). Vessels are dynamic and can change their permeability and undergo lymphangiogenesis under different stimuli.…”
Section: Introductionmentioning
confidence: 99%